Proceedings.Twenty-First Annual Joint Conference of the IEEE Computer and Communications Societies
DOI: 10.1109/infcom.2002.1019299
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive load sharing for network processors

Abstract: A novel scheme for processing packets in a router is presented, which provides for load sharing among multiple network processors distributed within the router. It is complemented by a feedback control mechanism designed to prevent processor overload. Incoming traffic is scheduled to multiple processors based on a deterministic mapping. The mapping formula is derived from the robust hash routing (also known as the highest random weight-HRW) scheme, introduced in K.W. Ross, IEEE Network, 11(6), 1997, and D.G. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 14 publications
0
49
0
Order By: Relevance
“…However, there are some limitations for using mobile agents in Active Networks. One of these restrictions is limited processing power of active nodes ( [10]- [12]). As the result, active nodes have limited power for hosting mobile agents and performing their management tasks.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are some limitations for using mobile agents in Active Networks. One of these restrictions is limited processing power of active nodes ( [10]- [12]). As the result, active nodes have limited power for hosting mobile agents and performing their management tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Although a number of adaptive load sharing policies are proposed in the literature [12], we found that the extended HRW technique [6] is suitable for network applications containing a number of flows. Hence, we implemented it in our system.…”
Section: Adaptive Load Sharing Policymentioning
confidence: 92%
“…As a result, most of the implementations are based on simple round-robin schemes. In this paper, we identify and implement a particular adaptive load balancing scheme [6] for our active router. We also propose a new stream-based round-robin policy that is simple but greatly reduces the out-of-order degree of the media units in a simple unit-based round-robin scheme.…”
Section: Figure 1 An Active Router In Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that round robin is simple and fast, but provides no guarantee to the playback quality of output streams because it causes out-oforder departure of processed media units [7]. Adaptive load sharing scheme, which we implemented from the literature [8], achieves better unit order in output streams, but involves higher overhead to map the media unit to an appropriate node. The aim of this paper is to derive a theoretical framework for load scheduling in a multimedia active router built with a network processor that comprises of a number of processors for packet processing.…”
Section: Fig 1 An Active Router In Networkmentioning
confidence: 99%